COVID-19: how prepared are front-line healthcare workers in England?. Issue 2 (June 2020) - Prescott, K.; Baxter, E.; Lynch, C.; Jassal, S.; Bashir, A.; Gray, J.
Summary: National efforts are underway to prepare the UK National Health Service (NHS) for the COVID-19 pandemic; however, the efficacy of these interventions is unknown. In view of this, a cross-sectional survey of front-line healthcare workers (HCWs) at two large acute NHS hospital trusts in England was undertaken to assess their confidence and perceived level of preparedness for the virus. The survey found that there has been moderate success in readying HCWs to manage COVID-19, but that more still needs to be done, particularly in relation to educating HCWs about laboratory diagnostics.